Purification of Cellulose and Chitin Polymers and Other Value-Added Products from the Microalga Chlorella vulgaris Using a Green Biorefinery Process - Enio Zanchetta; Baptiste Mercier; Maxime Frabboni; Eya Damergi; Christian Ludwig; Horst Pick (Fermentation)
Microalgae produce renewable biomass at high efficiency by using photosynthesis to capture the greenhouse gas CO2 from the atmosphere and releasing O2. Chlorella vulgaris is one of the most frequently cultivated unicellular green microalgae of commercial relevance. Some recent studies remarkably indicate that these microalgae can be a source of both cellulose and chitin biopolymers. Biomaterials produced with these polymers have useful mechanical properties. They are biocompatible and biodegradable, and they are regarded as sustainable alternatives to replace fossil-based bioplastics for many applications. However, selective and environmentally friendly processes for the effective co-purification of both polymers from microalgae are not yet available. Here, we present a green biorefinery approach that allowed, on the one hand, for the co-extraction of chitin and cellulose with a mass yield of 0.6% of the C. vulgaris biomass dry weight (before extraction). On the other hand, our method enabled to co-purify lipids, pigments, and proteins (mass yields: ~6.25%, ~0.13%, and ~50% of biomass dry weight, respectively) to make the whole procedure economically more viable. Finally, our greener fractionation and purification process was shown to reach efficiencies comparable to conventional, more toxic solvent extractions.